1987
DOI: 10.1128/jb.169.8.3482-3488.1987
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of bialaphos biosynthesis in Streptomyces hygroscopicus

Abstract: A DNA sequence (brpA) which regulates the expression of the genes of the bialaphos biosynthesis pathway (bap) in Streptomyces hygroscopicus was identfied and characterized. A newly isolated nonproducing mutant (NP57) had a pleiotropic defect involving at least 6 of the 13 known bap genes; only the step 6 conversion could be detected. NP57 was more sensitive to bialaphos than its parent and had depressed levels of the demethylphosphinothricin acetyltransferase activity (step 10 in the pathway) which confers bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
32
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 30 publications
(16 reference statements)
0
32
0
Order By: Relevance
“…Alternatively, some intermediate may be the in vivo substrate for Ard2. This is the case in Streptomyces strains that produce streptomycin, which occurs via phosphorylated intermediates (Mansouri and Piepersberg, 1991), and in the synthesis of bialaphos and puromycin, where an intermediate is acetylated (Anzai et al, 1987;Vara et al, 1985). In these three cases the antibiotics are finally activated during or after cell exclusion by specific hydrolases which remove the inactivating group (Lacalle et a]., 1993;Mansouri and Piepersberg, 1991;Raibaud et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, some intermediate may be the in vivo substrate for Ard2. This is the case in Streptomyces strains that produce streptomycin, which occurs via phosphorylated intermediates (Mansouri and Piepersberg, 1991), and in the synthesis of bialaphos and puromycin, where an intermediate is acetylated (Anzai et al, 1987;Vara et al, 1985). In these three cases the antibiotics are finally activated during or after cell exclusion by specific hydrolases which remove the inactivating group (Lacalle et a]., 1993;Mansouri and Piepersberg, 1991;Raibaud et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…For the first three compounds, it has been reported that their biosynthesis is controlled by the action of specific regulatory genes located within the particular biosynthetic clusters (4,(7)(8)(9). Such regulatory genes have also been identified in other antibiotic clusters, such as bialaphos (10), streptomycin (11,12), and daunorubicin (13).…”
mentioning
confidence: 99%
“…Work with other species has established that the Streptomyces hygroscopicus brpA (1,43) and Streptomyces griseus strR (10,23,39,42) (9,53) genes also fall into one of these groups. Some of the features of these protein families resemble the well-studied two-component regulatory systems of other bacteria (13,48).…”
mentioning
confidence: 99%